2021
DOI: 10.18089/tms.2021.170202
|View full text |Cite
|
Sign up to set email alerts
|

Tourists' perceptions of beach quality improvement during the off-peak season: a segmentation approach

Abstract: Recently coastal tourism has increased rapidly and has negatively affected environmental, social and cultural sustainability. The Algarve is the main sun-and-sea tourism destination in Portugal, with a large number of beautiful beaches. Due to negative tourism impacts and climate change, coastal tourism management tools need to be assessed and implemented. Most beach areas have the dual mandate of conserving coastal natural resources and providing opportunities for recreation and tourism. This paper aims to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Clustering has been conducted for regions [7][8][9] and tourist destination sites [10][11]. The efficient indicators, important attributes, inefficient behaviour, and popular destinations can be obtained by this analysis so that cooperation among regions can increase tourism competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering has been conducted for regions [7][8][9] and tourist destination sites [10][11]. The efficient indicators, important attributes, inefficient behaviour, and popular destinations can be obtained by this analysis so that cooperation among regions can increase tourism competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Lukoseviciute and Pereira [8] found that the rapid increase in coastal tourism negatively affected vital coastal and beach environments, as well as social and cultural sustainability. The equipment, services, and access needed to measure tourists' perceptions of beach quality are wildlife, vegetation, biodiversity, sand dunes, trails and boardwalks, seawater, garbage facilities, public toilets, showers, cafés/bars, and renewable energy.…”
Section: Introductionmentioning
confidence: 99%